2023
DOI: 10.1002/app.53683
|View full text |Cite
|
Sign up to set email alerts
|

Sequence distribution determination by SWAMP‐MS a systematic way of analyzing multiple fragmented polymers with mass spectrometry

Abstract: A new method to determine the blockiness and especially the block length distribution (BLD) of copolymers is described. This Systematic Workflow to Analyze Multi-fragmented Polymers with Mass Spectrometry (SWAMP-MS) is developed to characterize the sequence distribution of synthetic polymers.Copolymerization of polyamide 4,6 and polyamide 4,10 is used as a model system. Supercharged polymer ions, generated by electrospray ionization, swamp the mass spectrum due to <1> different chemical related distributions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Mengerink et al demonstrated multiple fragmentation in the MS to study BLD of polyamide copolymers. 114 The sample was first subjected to an LC separation and subsequently transformed ( i.e. fragmented) by MS/MS to identify co-oligomeric fragments.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Mengerink et al demonstrated multiple fragmentation in the MS to study BLD of polyamide copolymers. 114 The sample was first subjected to an LC separation and subsequently transformed ( i.e. fragmented) by MS/MS to identify co-oligomeric fragments.…”
Section: Synthetic Polymersmentioning
confidence: 99%